The Effect of Liquidity, Solvency, Profitability, and Activity on Company Value: Empirical Study on Tourism and Recreation Subsector Companies Listed on the Indonesia Stock Exchange for the Period 2018-2022 - Wahyuni, Hesti; Said, Said (CNPLUS Publisher, 2025)
ABSTRACT This research aims to determine the effect of current ratio, debt to equity ratio, net profit margin, and total assets turnover on the value of tourism and recreation subsector companies listed on the Indonesia Stock Exchange for the period 2018-2022. The data used in this research is secondary data in the form of financial reports of tourism and recreation subsector companies listed on the Indonesia Stock Exchange for the period 2018-2022. The sampling technique used was purposive sampling method based on specific criteria, resulting in a sample of 11 out of 19 companies. The analytical method used is multiple linear regression analysis and tested using the Statistical Package for the Social Science (SPSS) version 25 program. The research results show that the variables current ratio, debt to equity ratio, and total assets turnover have a positive and significant effect on company value. Meanwhile, net profit margin does not have a significant influence on company value.